Tingkat Kecemasan Matematika Siswa SMA Negeri 2 Kerinci Kelas X MIA Sebelum Menghadapi Tes Matematika Berdasarkan Gender dan Hubungannya dengan Hasil Belajar - Irel Nofrialdi; Maison Maison; Muslim Muslim (Edumatika : Jurnal Riset Pendidikan Matematika, 2018)
This research aims to determine differences in student anxiety levels based on gender and the relationship between students' anxiety levels before facing a mathematical test with achievement and then dig deeper information about the causes of anxiety in students. This research uses a mixed-method with a sequential explanatory approach. The subjects of this study were students of class X MIA Kerinci Senior High School 2 totaling 100 students. The results of the research showed that students experiencing anxiety before taking a math test as the cause of anxiety is experience, intelligence, preparation, and family. Differences in levels of anxiety based on gender indicate that there is no significant difference between the level of anxiety experienced by male and female students but male students are more anxious than female students the cause is that there have been similar thoughts and goals in terms of achievement so as to make male students neither men nor women experience significant differences in anxiety levels. There is a relationship between the level of anxiety with learning outcomes of 0.43 which is in the category enough and has a positive relationship, namely the higher the level of anxiety, the higher the student learning outcomes. Descriptions of quantitative data indicate that there is no certainty for someone who has an anxiety level will get a definite value.